Treatment of Subungual Exostosis: A Case Report (Bangladesh Journal of Medical Science, 2026)
Background Subungual exostosis is a rare benign osteocartilaginous tumor that occurs beneath the nail, often affecting the great toe (hallux). It typically presents as a painful, growing subungual mass causing nail deformity. Trauma or chronic irritation is thought to play a role in its etiology. Case We report a case of a 14-year-old boy with a one-year history of a painful subungual mass on the right great toe following trauma. The lesion gradually enlarged, causing nail elevation, erythema, and difficulty in daily activities. Examination revealed a firm, fixed nodule under the nail plate. Radiographs demonstrated a pedunculated bony outgrowth from the dorsal distal phalanx. Conservative management for six months failed to relieve symptoms. The patient underwent surgical excision under digital block anesthesia. The nail fold was carefully elevated, and the exostosis was removed en bloc using an osteotome and rongeur. Histopathology confirmed mature trabecular bone with a cartilaginous cap, consistent with subungual exostosis. Outcome Recovery was uneventful. The nail was preserved with minimal deformity, and no recurrence was noted at 12-month follow-up. This case highlights the importance of recognizing subungual exostosis and the efficacy of complete surgical excision. Conclusion Timely diagnosis and surgical treatment of subungual exostosis can alleviate pain and prevent nail deformity. Our literature review emphasizes trauma as a common precipitating factor and supports complete lesion excision (including the base) to minimize recurrence.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S369-S374